Ependymoblastoma of the brainstem: MRI findings and differential diagnosis. Issue 6 (25th January 2014) - Nowak, Johannes; Seidel, Carolin; Pietsch, Torsten; Friedrich, Carsten; von Hoff, Katja; Rutkowski, Stefan; Warmuth‐Metz, Monika
<x xml:space="preserve">Abstract</x> Ependymoblastoma (EBL) is a rare malignant CNS tumor of early childhood, listed as a subgroup of primitive neuroectodermal tumors (PNET) in the 2007 WHO Classification of Tumours of the Central Nervous System. Histologically, EBL can be defined by multilayered, mitotically active "ependymoblastic" rosettes with central lumen as a histological hallmark. The prognosis seems to be far inferior to other embryonal CNS tumors, and known clinical and MRI characteristics of EBL are based on scattered case reports. We present and discuss two uncommon cases of histopathologically confirmed ependymoblastoma that both seem to originate from the brainstem. Pediatr Blood Cancer 2014;61:1132–1134. © 2014 Wiley Periodicals, Inc.